Forming Entrepreneurial Competences: Interaction of Universities and Business (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The paper discusses the issues of forming entrepreneurial competencies and the solving problems of entrepreneurial education in the interaction between universities and business. The analysis of the advantages and disadvantages of the competency-based approach from theoretical and practical positions is undertaken. Approaches to identifying entrepreneurial behavior are proposed. The necessity of revising a number of provisions that are currently considered as the integral characteristics of entrepreneurial activity is substantiated. Forms of interaction between universities and business are proposed, which allow building relationships on a mutually beneficial basis. The necessity of expanding the use of active and interactive teaching methods in entrepreneurial education is substantiated. The requirements to the level of entrepreneurial competencies of a university teacher involved in the training of entrepreneurs are formulated.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.